Factors associated with diverticular bleeding and re-bleeding: A United States hospital study - Jalil, Ala Abdel (North Clin Istanb, 2018)
OBJECTIVE: Diverticular bleeding is the most common cause of lower gastrointestinal bleeding. Arteriovascular disease, metabolic syndromes, non-steroidal anti-inflammatory drugs (NSAIDs), anti-thrombotics, and anticoagulants have been suggested as risk factors. There is a paucity of studies addressing factors associated with diverticular re-bleeding, especially in the United States. The aim of this study is to evaluate factors associated with colonic diverticular bleeding and re-bleeding in a US community-based hospital. METHODS: We conducted a retrospective case-control study to analyze the factors associated with diverticular bleeding. Between January 2010 and July 2011, 93 patients were admitted to our hospital with a primary diagnosis of acute diverticular bleeding. We compared them to 152 patients who were admitted with a primary diagnosis of diverticulitis in the same period. We collected data from the medical records of each patient in relation to the demographics, comorbidities, medications, social habits, location of diverticulosis, length of stay in the hospital, and re-bleeding rate within 2 years of the first bleeding episode. RESULTS: Factors such as cerebrovascular accident (p=0.009), coronary artery disease (p=0.037), diabetes mellitus (p=0.046), obstructive sleep apnea (p=0.033), NSAIDs (p=0.038), use of anti-thrombotics (p=0.001), anticoagulants (p=0.002) or calcium channel blockers (p=0.009), and bilateral diverticulosis (p=0.001) were significantly associated with diverticular bleeding as compared to diverticulitis. Recurrence of bleeding was noted in 26 out of 93 patients (28%) within 2 years of the first bleeding episode (p=0.001). Bilateral colonic involvement, anticoagulants, and elderly age (≥65 years) were found to have a closer relationship to diverticular re-bleeding, although it was not statistically significant. CONCLUSION: This study reveals that arteriovascular disease, diabetes mellitus, NSAIDs, the use of anti-thrombotics, anticoagulants or calcium channel blockers, and obstructive sleep apnea are factors that are significantly associated with diverticular bleeding. It also shows that bilateral colonic involvement, elderly age, and anticoagulants have a closer relationship to diverticular re-bleeding. More prospective studies in patients with diverticular bleeding should be conducted to shed light on the causality of these factors and the prevalence of diverticulitis.